2021
DOI: 10.3390/ijerph18084143
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Psychological Responses among the Public during the Early Phase of COVID-19: A Cross-Regional Analysis

Abstract: This study aimed to compare the mediation of psychological flexibility, prosociality and coping in the impacts of illness perceptions toward COVID-19 on mental health among seven regions. Convenience sampled online survey was conducted between April and June 2020 from 9130 citizens in 21 countries. Illness perceptions toward COVID-19, psychological flexibility, prosociality, coping and mental health, socio-demographics, lockdown-related variables and COVID-19 status were assessed. Results showed that psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 70 publications
1
19
0
Order By: Relevance
“…Studies investigating factors of psychological resilience, i.e., the ability to adapt positively and bounce back from adversity [ 28 ], during the pandemic found a negative relationship between resilience and mental health problems such as depression, anxiety and somatization [ 29 31 ]. Specifically, empirical studies have shown that greater social support, higher levels of mindfulness, cognitive control over emotions, and greater psychological flexibility predict the relationship between illness perceptions, resilience and mental health problems [ 15 , 21 , 27 , 32 ]. This indicates that individuals who were able to obtain more social support, and who were able to flexibly adapt their coping strategies in the face of distress, showed the most positive mental health outcomes during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies investigating factors of psychological resilience, i.e., the ability to adapt positively and bounce back from adversity [ 28 ], during the pandemic found a negative relationship between resilience and mental health problems such as depression, anxiety and somatization [ 29 31 ]. Specifically, empirical studies have shown that greater social support, higher levels of mindfulness, cognitive control over emotions, and greater psychological flexibility predict the relationship between illness perceptions, resilience and mental health problems [ 15 , 21 , 27 , 32 ]. This indicates that individuals who were able to obtain more social support, and who were able to flexibly adapt their coping strategies in the face of distress, showed the most positive mental health outcomes during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a recent study found that fear of compassion predicted worse mental health and lower social safeness and closeness, suggesting a protective role of compassion in predicting mental well-being during the pandemic [ 35 ]. Similarly, increased prosocial behavior also served as a protective factor mediating the relationship between perception of COVID-19 and mental health symptoms [ 32 ]. On the other hand, studies also showed decline in empathic concern and prosocial behavior in adolescents as a result of the lockdown [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that studies conducted in other period of the pandemic would find a different pattern of results. In fact, a study with a very large cross-regional sample collected from April to June 2020 [ 57 ] found that social support strategies positively mediated the effect of perceived severity of COVID-19 disease and mental health, with perception of illness that increased social support seeking, which in turn increased well-being. This result was in contradiction with ours, but our data was collected in April 2020 while their data [ 57 ] was collected later, when most of the restrictive measures relaxed over time in Italy as in many other countries.…”
Section: Discussionmentioning
confidence: 99%
“…Half of HCPs and up to 90% of patients affected by COVID-19 have reported high rates of anxiety, depression, post-traumatic stress disorder, and other mental health issues ( Bo et al, 2020 ; Lai et al, 2020 ). Furthermore, unlike the SARS epidemic, global reports note considerable increases in psychological distress throughout the general population; not just those directly affected by the virus ( Alhalafi, 2020 ; Chong et al, 2021 ; Ettman et al, 2020 ; Gloster, Lamnisos, et al, 2020 ; Rossi et al, 2020 ; Wang et al, 2020 ). In a recent large-scale UK survey, over half of respondents met criteria for common mental health conditions ( Pieh et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%